ASPEK KE-SOEHARTO-AN DALAM KUMPULAN CERPEN SOEHARTO DALAM CERPEN INDONESIA - Burhan Nurgiyantoro (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2005)
This research study aims to describe (1) the forms of Soeharto-related aspectsand (2) ways of expressing those aspects in the anthology of short stories entitledSuharto claim Cerpen Indonesia.The source of the research data was Soeharto dalam cerpen Indonesia (2001), ananthology of short stories edited by M. Shoim Anwar. All of the short stories (17)were selected. The data were collected through reading and recording techniques andwere analyzed by the descriptive qualitative technique involving data comparison,categorization, tabulation, and inference. Data trustworthiness was assessed throughthe semantic and referential validities and data consistency through the intraratertechnique.Research findings show that 15 short stories clearly contain Soeharto-relatedaspects, and two short stories do not reveal these aspects clearly. Soeharto-relatedaspects are shown through: (1) personification in the form of physical appearance,character, verbal and nonverbal behaviors, (ii) governance and economic strategies,(iii) society’s condition and attitude under his reign, approaching his fall and after hisfall, (iv) spatial and temporal settings related to his reign, (v) the party functioning ashis power apparatus, and (vi) government officials’ life style and attitude. In generalthe short stories do not mention Soeharto directly, but only through certain aspectsor symbols easily identified as Soeharto’s characteristics. Soeharto-related aspectsare expressed through various ways, such as parody, irony, cynicism, and dialectics.The expressions through particular characters parodying Soeharto are the mostapparent, simultaneously using irony and cynicism. The expressions through ironyare the most dominant in the short stories, and in this way the criticisms sound moresubtle and “polite”. This is different from cynicism, which criticizes and defamesones in a vulgar manner. This is a reflection of control imposed on the writers in thepast, who now feel free to express anything without any fear of being arrested. Theexpressions through dialectics are made more intellectually and invite readers tothink.Key words: Soeharto-related aspects, personification, parody, irony, cynicism,dialectics